Migrations in ageing society: consequences for the family, selected challenges for social policy - Wieczorkowska, Magdalena; Pawlak, Agnieszka (Studia Demograficzne, 2020)
Labour migration of people at productive age is a common practice in Western countries based on capitalist economy and parliamentary democracy. Post-accession migration from Poland is a mass phenomenon nowadays, having a double impact on the situation of the oldest family members: they face the need to undertake new versions of old traditional roles or – on the other hand – they are left alone, often in deteriorating health conditions and without assistance in everyday routines. The aim of this analysis is to provide recommendations for social policy on possible solutions supporting and supplementing the care offered for old persons in the situation of migration of their adult children. The analysis is based on the existing data and reports. Recommendations proposed in the article are directly and indirectly related to forms of care which should be provided to older adults. Aid and assistance are viewed as a chain of interrelated processes; for example, higher digital competences of older adults would allow them to communicate with their families abroad and would help them to be independent in shopping or fixing financial and administrative affairs, as they could do this online.